BILL OF MATERIAL (BOM) PADA SISTEM INVENTORI KAWASAN BERIKAT UNTUK PELACAKAN MATERIAL MOVEMENT - Sari, Betha Nurina; Komarudin, Oman; Padilah, Tesa Nur; Nurhusaeni, Muhamad (ILKOM Jurnal Ilmiah, 2018)
A manufacturing company processes raw material into semi-finished goods (work in process) and finished goods. One injection molding manufacturing company in Karawang manufactures plastic materials for printing into various forms of vehicle safety equipment. The three main processes that occur from raw materials to finished goods are the storage of raw material in the warehouse, the process of changing raw material into finish goods in the production area, and storage of finish goods to be sent to the customer. Bill of Material (BOM) is designed to contain all changes in shape so that it is easier to calculate raw material requirements and tracking material movements. This information system is designed using the Extreme Programming (XP) method. The results of this study help the management of manufactured goods in Injection Molding Manufacturing Company from starting raw material, work in process, to being a good finish needed by the company to track goods data and to fulfill the real time reporting interests requested by Bea Cukai.